EFFECT OF REWARD AND JOB COMFORT ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE (CASE STUDY: PT. MERAKI DIGITAL INDONESIA) - Adam Hasbi Nugroho; Muhammad Havidz Aima (Dinasti Publisher, 2022)
This study aims to identify and explain the effect of reward and job comfort against employee performance with job satisfaction as a mediating variable (Case Study: PT. Meraki Digital Indonesia). This research is a quantitative research with 420 employees of PT. Meraki Digital Indonesia as a population. The sampling technique is non-probability sampling with 150 permanent employees as a sample. Data sources from primary and secondary data. The data analysis method uses SEM-PLS with SmartPLS software 3.2.9 version. The results showed that: (1) Reward and job comfort both partially and simultaneously has a positive and significant effect on job satisfaction; (2) Reward, job comfort, and job satisfaction both partially and simultaneously has a positive and significant effect on employee performance; and (3) Job satisfaction has a positive and significant effect in mediating reward and job comfort on employee performance.